A Technique for the In Vivo Study of Three-dimensional Cervical Segmental Motion Characteristics After Anterior Screw Fixation for Odontoid Process Fractures. Issue 7 (1st April 2021) - Zhong, Yanlong; Yao, Haoqun; Tang, Benyu; Song, Quanwei; Shaobai, Wang; Li, Guoan; Wan, Zongmiao
Abstract : Study Design: Kinematics of the cervical spine was investigated using cone beam computed tomography (CBCT) images combined with three dimensions to three dimensions (3D-3D) registration technology in patients after anterior odontoid screw fixation (AOSF) surgery. Objective: The aim of this study was to investigate in vivo 3D cervical motion characteristics of patients who had undergone AOSF surgeries. Summary of Background Data: AOSF surgery is a classic surgical method for the treatment of odontoid fracture, but there are few studies that investigated its effect on in vivo biomechanics of the cervical spine. Postoperative biomechanical characters of the atlantoaxial joint (C1-C2) and the caudal adjacent segment (C2–C3) have yet to be clarified. Methods: The study involved 14 patients subjected to a procedure of AOSF with lag screw. Subjects were matched with 14 healthy controls. All subjects underwent CBCT scanning of the cervical spine under seven functional positions. A 3D-3D registration was performed for each vertebra at each functional position to calculate the segmental motion characteristics. The ranges of motion (ROMs) of the C1-C2, C2–C3, and the overall cervical spine (C1-C7) for each of the functional positions were determined. Results: The ROMs of the AOSF group were significantly ( P < 0.05) smaller than the control group in flexion-extension positions for the C1-C2 (7.0° vs .11.0°), C2-C3 (3.7° vs .6.7°) and C1-C7 (43.3° vs .54.4°). The twisting ROM of the C1-C2 was 39.3° in the AOSF group and 65.7° in the control ( P < 0.05), the bending ROM of the C2-C3 was 2.8° in the AOSF group and 8.9° in the control ( P < 0.05). The twisting ROM of C1-C7 segment was 63.2° for the AOSF and 98.1° for the healthy control groups ( P < 0.05). Conclusion: Although AOSF surgery reduced the flexion-extension ROMs of all investigated spinal segments, additionally, it reduced twisting ROMs of C1-C2 and C1-C7, but only lateral bending ROM of C2-C3, when compared with the control group. The data implied that the AOSF surgery would result in different biomechanics changes in the atlantoaxial segment and caudal adjacent segment. Longer-term follow-up studies of larger patient cohorts are necessary to evaluate the clinical outcomes of patients after the AOSF surgery. Level of Evidence: 3 Abstract : The aim of this study was to investigate in vivo three dimensions (3D) cervical motion characteristics of patents who had undergone anterior odontoid screw fixation surgery using cone beam computed tomography images combined with 3D-3D registration technology. The 6 degrees-of-freedom kinematics of atlantoaxial joint and the adjacent segment C2-C3 as well as compensatory movements of subaxial cervical spine were precisely evaluated.